Bioactivity of Cod and Chicken Protein Hydrolysates before and after in vitro Gastrointestinal Digestion - Jamnik, Polona; Istenič, Katja; Koštomaj, Tatjana; Wulff, Tune; Geirsdóttir, Margrét; Almgren, Annette; Jónsdóttir, Rósa; Kristinsson, Hordur G.; Undeland, Ingrid (Food Technology and Biotechnology, 2017)
Summary Bioactivity of cod (Gadus morhua) and chicken (Gallus domesticus) protein hydrolysates before and after in vitro gastrointestinal (GI) digestion was investigated using yeast Saccharomyces cerevisiae as a model organism. Both hydrolysates were exposed to in vitro GI digestion prior to cellular exposure to simulate digestion conditions in the human body and therefore investigate the role of modulations in the GI tract on the cell response. The effect of digested and undigested hydrolysates on intracellular oxidation, cellular metabolic energy and proteome level was investigated. No difference in the effect on intracellular oxidation activity was obtained between cod and chicken hydrolysates, while higher affect on intracellular oxidation was provided by digested hydrolysates, with relative values of intracellular oxidation of cod of (70.2±0.8) and chicken of (74.5±1.4) % than by undigested ones, where values of cod and chicken were (95.5±1.2) and (90.5±0.7) %, respectively. Neither species nor digestion had any effect on cellular metabolic energy. At proteome level, digested hydrolysates gave again significantly stronger responses than undigested counterparts; cod peptides here also gave somewhat stronger response than chicken peptides. The knowledge of the action of food protein hydrolysates and their digests within live cells, also at proteome level, is important for further validation of their activity in higher eukaryotes to develop new functional food ingredients, such as in this case chicken and cod muscle-derived peptides.